2019
DOI: 10.1097/corr.0000000000000716
|View full text |Cite
|
Sign up to set email alerts
|

CORR Insights®: Is Parkinson’s Disease Associated with Increased Mortality, Poorer Outcomes Scores, and Revision Risk After THA? Findings from the Swedish Hip Arthroplasty Register

Abstract: The author certifies that neither he, nor any members of his immediate family, have any commercial associations (such as consultancies, stock ownership, equity interest, patent/licensing arrangements, etc.) that might pose a conflict of interest in connection with the submitted article. All ICMJE Conflict of Interest Forms for authors and Clinical Orthopaedics and Related Research ® editors and board members are on file with the publication and can be viewed on request. The opinions expressed are those of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The reason may be that elderly patients with Parkinson’s disease experience limb tremors, muscle tonicity, and difficulty in maintaining abduction neutral position when lying down, and are prone to internal retraction and internal rotation movements leading to hip dislocation, and PLA may cause periarticular soft tissue injury, resulting in hip instability after hip arthroplasty. The present study showed no statistically significant difference in the postoperative hip prosthesis position between the 2 groups, which was consistent with the research results by Giori et al [ 21 ]. The reason may be that DAA separates the deep fascia of the thigh from the gap between the broad fascial tensor and rectus femoris to expose the hip joint without cutting any muscle tendon.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The reason may be that elderly patients with Parkinson’s disease experience limb tremors, muscle tonicity, and difficulty in maintaining abduction neutral position when lying down, and are prone to internal retraction and internal rotation movements leading to hip dislocation, and PLA may cause periarticular soft tissue injury, resulting in hip instability after hip arthroplasty. The present study showed no statistically significant difference in the postoperative hip prosthesis position between the 2 groups, which was consistent with the research results by Giori et al [ 21 ]. The reason may be that DAA separates the deep fascia of the thigh from the gap between the broad fascial tensor and rectus femoris to expose the hip joint without cutting any muscle tendon.…”
Section: Discussionsupporting
confidence: 94%
“…Xu et al [ 20 ] used a multifactorial statistical analysis to demonstrate that PLA surgery in patients with Parkinson’s disease was more likely to cause hip instability, leading to a higher incidence of dislocation, which was attributed to excessive destruction of the posterior joint capsule and externally rotated muscle groups by PLA; therefore, an anterior or lateral approach was recommended. Giori et al [ 21 ] found that the rate of dislocation with DAA in patients with combined Parkinson’s disease was (2.2%) similar to that of patients without Parkinson’s (1.9%), suggesting a lower postoperative dislocation rate with DAA in patients with concomitant Parkinson’s disease. The results of the present study demonstrated that the incidence of PLA hip dislocation was higher than that of PLA hip dislocation in patients without Parkinson’s disease (4.4%).…”
Section: Discussionmentioning
confidence: 99%